2017
DOI: 10.1007/s40139-017-0141-y
|View full text |Cite
|
Sign up to set email alerts
|

Using Zebrafish to Model Liver Diseases-Where Do We Stand?

Abstract: Purpose of Review The liver is the largest internal organ and performs both exocrine and endocrine function that is necessary for survival. Liver failure is among the leading causes of death and represents a major global health burden. Liver transplantation is the only effective treatment for end-stage liver diseases. Animal models advance our understanding of liver disease etiology and hold promise for the development of alternative therapies. Zebrafish has become an increasingly popular system for modeling l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 143 publications
(122 reference statements)
0
24
0
2
Order By: Relevance
“…• All major mammalian liver cell types are present except Kupffer cells, cell type-specific functions are largely conserved (Goessling and Sadler, 2015;Pham et al, 2017) • Bile secretion via bile canaliculi (Goessling and Sadler, 2015;Pham et al, 2017) • Kupffer cells are not observed (Goessling and Sadler, 2015;Pham et al, 2017) • Different cellular architecture (i.e., hepatocytes arranged into tubules, lobules and portal triads not present; Goessling and Sadler, 2015;Pham et al, 2017) Pancreas…”
Section: Geneticsmentioning
confidence: 99%
“…• All major mammalian liver cell types are present except Kupffer cells, cell type-specific functions are largely conserved (Goessling and Sadler, 2015;Pham et al, 2017) • Bile secretion via bile canaliculi (Goessling and Sadler, 2015;Pham et al, 2017) • Kupffer cells are not observed (Goessling and Sadler, 2015;Pham et al, 2017) • Different cellular architecture (i.e., hepatocytes arranged into tubules, lobules and portal triads not present; Goessling and Sadler, 2015;Pham et al, 2017) Pancreas…”
Section: Geneticsmentioning
confidence: 99%
“…The teleost zebrafish, an increasingly popular vertebrate model for studying development and genetics, has shown promise in bringing new insights into our understanding of the ontogeny of liver macrophages and their responses to injury. Zebrafish form a functional liver by just 4 days post fertilization (6). Despite some architectural differences, the zebrafish liver contains a highly similar parenchymal and non-parenchymal cell inventory as the mammalian liver.…”
Section: Introductionmentioning
confidence: 99%
“…Despite some architectural differences, the zebrafish liver contains a highly similar parenchymal and non-parenchymal cell inventory as the mammalian liver. Taking advantages of the transparent larva and the accessibility to genetic manipulation, researchers have generated transgenic fluorescent reporter strains to mark individual liver cell types, enabling real-time tracking of their morphology and behaviors during development and injury (6). Zebrafish have been used in translational research modeling various liver diseases such as drug-induced acute liver failure, cholestasis, non-alcoholic liver disease, alcoholic liver disease, and cancer (68).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the hybrid human/rat WIF-B9 cell line was chosen due to its high level of differentiation into hepatocyte and its sensitivity to low concentrations of chemicals, notably alcohol 27 , 28 , compared to HepaRG cells; such a feature appears to be interesting when studying concentrations of chemicals relevant to human exposure. Finally, we focused our study on the zebrafish larva model to test in vivo our hypothesis; indeed this model is now well recognized as sharing pathophysiological processes with human, especially concerning liver diseases, with advantages of time and cost-efficiency in comparison to mammal or rodent models 29 31 .…”
Section: Introductionmentioning
confidence: 99%